Persepsi Siswa Terhadap Pembelajaran E-Learning Selama Pandemi Covid-19 Di Program Studi Pendidikan Guru Sekolah Dasar (PGSD) STKIP PGRI Banjarmasin - Fathul Zannah; Noormaliah (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
In practice, online learning faces several obstacles. that need to be considered and considered by paying attention to models, strategies, learning outcomes, the availability of facilities that support learning for both students and lecturers. This is the basis for research on student perceptions of the primary school teacher education study program (PGSD) STKIP PGRI Banjarmasin. The purpose of this study was to determine students' towards online learning applied at STKIP PGRI Banjarmasin. Researchers get data for this study from questionnaires and interviews. The questionnaire contains student perceptions of online lectures which are divided into several indicators, namely accessibility, device ownership, ease of obtaining materials and doing assignments, understanding of teaching materials, learning methods, interactivity, independent learning and the environment. The questionnaire uses a Likert scale. The results of the questionnaire were re-confirmed through interviews with several students and lecturers. The results of this study indicate that 71% of students agree with online lectures conducted by STKIP PGRI Banjarmasin and 29% of students disagree with online lectures conducted by STKIP PGRI Banjarmasin. Students agree with the online learning system at SKIP PGRI Banjarmasin based on accessibility indicators (33%), device ownership (38%), monitoring ability (76%), ease of obtaining materials and doing assignments (67%), understanding of teaching materials (52%) , teaching methods (86%), interactivity (86%), independent learning (67%), environmental support (76%). In its implementation, there are several obstacles, especially in terms of accessibility and ownership of devices which often experience problems with internet access both in terms of quantity and quality.